Pemberdayaan Perangkat Desa Pajar Bulan dalam Pembuatan Media Informasi dan Administrasi Publik melalui Pelatihan Canva - Yohanes Susanto; Wita Hairani; Shinta Wiji Rahayu (Bengkulu Institute, 2025)
Village officials play a vital role in delivering public services and disseminating information to the community. However, limited skills in managing digital information media and preparing public administrative documents often hinder the realization of effective and transparent services. This program aims to enhance the capacity of village officials in Pajar Bulan Village, Kaur Tengah District, Kaur Regency, through training on the use of Canva as a tool for creating attractive, efficient, and professional information media and public administrative documents. The methods applied include interactive training sessions, practical mentoring, and evaluation of participants’ works. The results of the program indicate an improvement in participants’ abilities to design pamphlets, circular letters, infographics, and digital-based village administrative reports. This activity is expected to encourage the independence of village officials in Pajar Bulan Village, Kaur Tengah District, Kaur Regency in managing public communication and administration in a more modern and effective manner.